Literasi Keuangan, Persepsi UMKM terhadap Kualitas Laporan Keuangan dengan Penerapan SAK EMKM - Ayulina Oktaviranti; Muhammad Iqbal Alamsyah (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to analyze how the influence of the quality of financial reports on Literasi Keuangan and the perceptions of MSME actors on the quality of financial reports, both directly and mediated by the application of SAK EMKM. The research method used is a quantitative method with a descriptive verification approach. The sample used is MSME actors in Bandung Regency. The sampling technique in this study was non-probability sampling with purposive sampling. The tool used in this study to analyze the relationship between variables is Partial Least Square (PLS) with SmartPLS 4.0. The results of the study show that Literasi Keuangan has no positive effect on the quality of financial reports. The perception of MSME actors does not have a positive impact on the quality of financial reports. Literasi Keuangan has a positive effect on the Penerapan SAK EMKM and Perceptions of MSME Actors have a positive effect on the Penerapan SAK EMKM. Furthermore, there is a positive influence from Literasi Keuangan on the quality of financial statements mediated by the application of SAK EMKM and a positive influence from the perceptions of MSME actors on the quality of financial reports mediated by the application of SAK EMKM.